Computers Bring New Oppotunities to Education & Training in Science & Technology - M. Bunjamin Bunjamin (Widyanuklida, 1998)
All of us at Pusdiklat know very well that our country, through the GBHN statements, and also Batan, through its mission & vision statements, stressed the highest priority of human resources development as an important element in our attempt to survive - even to make progress - in the 21st century that will come soon. Naturally, as the education & training center of Batan, Pusdiklat must shoulder most of this heavy burden. Unfortunately, with our limited education & training budget, especially in the face of our country's problem of financial crisis, the burden on Pusdiklat's shoulders is extra heavy, and we really have to think and work very hard to accomplish Pusdiklat's "mission impossible".